The Effects On Groundwater Of A Proposed Ash Disposal Operation At An East Texas Lignite Mine - K. A. Wheeler (Society for Mining, Metallurgy & Exploration, 1994)
To evaluate the effects on groundwater of a proposed in-pit disposal operation at an east Texas lignite mine, the local geologic, hydrogeologic, and geochemical features were thoroughly characterized. Resultant data were used in a flow and transport model (SWIFT) to simulate migration of the ash leachate. Computer simulations indicate that the leachate plume will travel 61-152 meters from the disposal area in 100 years after resaturation of the spoils. A 61-meter buffer zone of mine spoils without ash will surround the disposal area. The proposed landfill operation received regulatory approval and is currently operating as a Class 2 non-hazardous landfill.